Local complications of intravenous injction site in burned children - Salman-yazdi N. (Iran University of Medical Sciences, 1999)
Background: Burned patients often need longterm intravenous therapy and may suffer from local and systemic complications . Objective: To determine the local complications of intravenous injections. Design: This was a longitudinal study. Data were collected by observing injection site during hospitalization which varied from 3 to 28 days. Sample: Fifty children up to 13 years of age who were admitted to burn hospitals during research course. Result: The Most Frequent complications were pain, redness and edema. Conclusion: Local complications of intravenous injections can be prevented Teaching staff nurses periodicaly could be helpful in taking care of these children. Further research are recommended to point out other preventive measures